Primary and secondary creativity. (June 2019) - Runco, Mark A; Beghetto, Ronald A
Abstract : Who decides what counts as creative? Although most creativity researchers would acknowledge that both individuals and broader social audiences can offer interpretations about creativity, the way in which researchers tend to conceptualize and study creativity typically focuses on either an individual or a social perspective. Those who focus on individual interpretations may treat the social superficially (if at all), whereas those who focus on social judgments risk minimizing or erasing the role of the individual. Consequently, the question of `Creativity for whom?' too often divides creativity research. In this article, we briefly review recent work in the field of creativity studies that falls along the lines of personal and social judgments of creativity. We introduce an integrative framework that endeavors to reconcile the divide between the personal and the social. Specifically, we introduce a model of Primary and Secondary Creativity, which illustrates how the one process of creativity can explain both personal and social judgments of creativity.